Fresno County Bar Association Bernie Witkin Luncheon at Fresno County Plaza Ballroom - Watkins, Howard::::::::: (1988)
Judges Jim Paige and Harold Thompson with Bernie Witkin seated at headtable Paige and Thompson met Witkin in early 1960's at Lakeshore Village and invited him to speak at the Fresno County Bar Association Bar